An analysis of intentions to reduce ICT- waste among MSC Malaysia Status Companies / Ng Tuan-Hock...[et.al] - Ng, Tuan-Hock; Lim, Ying-San; Lye, Chun-Teck; Ismail, Hishamuddin; Tan, Mei-Chee (Universiti Teknologi MARA, Cawangan Melaka, 2019)
An upsurge in consumption of information and communication technology (ICT) products has ignited conflicting debate about the impacts of ICT. On the one hand, ICT accelerates productivity, but on the other hand, environmental degradation issues associated with the rise in the amount of ICT-waste are a matter of deep concern for all. When waste issues come into focus, there is a growing need for long-term solutions. In this context, 'reduce' has been hailed as an effective ICT-waste prevention method by environmentalists and policymakers. Nonetheless, empirical evidence in this discussion remains sparse. The primary objective of this study is to investigate the determining factors of 'reduce' intention among employees in companies with MSC Malaysia status. Premised on the classic theory of planned behaviour (TPB) and survey analysis, this study reports that attitude, subjective norms and perceived behavioural controls are significant predictors of 'reduce' intention. The recommendations put forth in this study consider governmental policies and corporate actions that potentially bring ICT-waste under control.